Method for determining effectiveness of cleaning devices for PM2.5 and PM10 suspended particles in dusty industrial emissions - L. O. Shtripling; V. V. Bazhenov; Yu. V. Kalinin; N. S. Bazhenova; V. V. Merkulov (Омский научный вестник)
The article deals with the issue of determining the fractional efficiency of dust collecting devices for PM2.5 and PM10 suspended particles. The need for the application of this method is indicated due to the increased risk of fine dust for health and more serious hygienic standards in comparison with general dust. The authors determined the composition of dust and the content of PM2.5 and PM10 fractions for dust removal equipment at the inlet and outlet analyzed the actual efficiency of fine dust and compared it with the efficiency indicated in the passport data. It is determined that the actual efficiency for fine dust may differ significantly from the passport data. A method for determining the fractional efficiency of dust collecting devices for fine dust is proposed.